2000
DOI: 10.1029/2000jc900029
|View full text |Cite
|
Sign up to set email alerts
|

Sea ice circulation in the Laptev Sea and ice export to the Arctic Ocean: Results from satellite remote sensing and numerical modeling

Abstract: Abstract. Sea ice circulation in the Laptev

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 22 publications
4
40
0
Order By: Relevance
“…The ice exchange of the Laptev Sea with surrounding seas were investigated for the first time by Zakharov (1966a) and Zakharov (1967) using monthly gradients of atmospheric pressure for the period between 1937 and 1958. According to Alexandrov et al (2000), the authors found the ice exchange between fall and spring to be within the range of our findings. However, the publication is available in Russian only, which makes a direct comparison with our estimates difficult.…”
Section: Discussion Of Area Flux Estimatessupporting
confidence: 62%
See 4 more Smart Citations
“…The ice exchange of the Laptev Sea with surrounding seas were investigated for the first time by Zakharov (1966a) and Zakharov (1967) using monthly gradients of atmospheric pressure for the period between 1937 and 1958. According to Alexandrov et al (2000), the authors found the ice exchange between fall and spring to be within the range of our findings. However, the publication is available in Russian only, which makes a direct comparison with our estimates difficult.…”
Section: Discussion Of Area Flux Estimatessupporting
confidence: 62%
“…However, the publication is available in Russian only, which makes a direct comparison with our estimates difficult. Sea ice circulation in the Laptev Sea and ice exchange with the Arctic Ocean have been further studied by Alexandrov et al (2000). The authors investigated ice exchange through the NB and EB based on a large-scale thermodynamic-dynamic sea ice model from 1979 to 1995.…”
Section: Discussion Of Area Flux Estimatesmentioning
confidence: 99%
See 3 more Smart Citations